Pro‐inflammatory role of natural killer cells in the development of allergic airway disease. Issue 4 (April 2014) - Mathias, C. B.; Guernsey, L. A.; Zammit, D.; Brammer, C.; Wu, C. A.; Thrall, R. S.; Aguila, H. L.
Summary Background Natural Killer (NK) cells have been implicated in the development of allergic airway inflammation. However, the in vivo role of NK cells has not been firmly established due to the lack of animal models with selective deficiencies in NK cells. Objective To determine the specific contribution of NK cells in a murine model of allergic airway disease (AAD). Methods The role of NK cells in AAD was studied using NK‐deficient (NKD) mice, perforin−/− mice, and mice depleted of Ly49A/D/G+ NK cell subsets in an ovalbumin‐induced model of allergic airway disease (OVA‐AAD). Results Induction of OVA‐AAD in C57BL/6 wild‐type (WT) mice resulted in the expansion of airway NK cells and the development of pronounced airway eosinophilia. In the absence of NK cells or specific subsets of NK cells, either in NKD mice, or after the depletion of Ly49A/D/G+ NK cells, the development of OVA‐AAD was significantly impaired as seen by decreased airway inflammation and eosinophilia, decreased secretion of the Th2 cytokines IL‐4, IL‐5 and IL‐13 and diminished OVA‐specific antibody production. Furthermore, while OVA‐exposure induced a dramatic expansion of dendritic cells (DCs) in WT mice, their induction was significantly attenuated in NKD mice. Development of OVA‐AAD in perforin−/− mice suggested that the proinflammatory role of NK cells is not dependent on perforin‐mediated cytotoxicity. Lastly, induction of allergic disease by OVA‐specific CD4 T cells from WT but not NK‐depleted or NKD mice in RAG−/− recipients, demonstrates that NK cells are essential for T cell priming. Conclusions and Clinical Relevance Our data demonstrate that conventional NK cells play an important and distinct role in the development of AAD. The presence of activated NK cells has been noted in patients with asthma. Understanding the mechanisms by which NK cells regulate allergic disease is therefore an important component of treatment approaches.